A triad of ventral hernia, cholelithiasis and uterine fibroid in females and ventral hernia, cholelithiasis and benign prostatic hypertrophy in males - Harika, D. Navya Sesha; Kumar, S. Raj; Sriram, Gandham; Lakshmi, J. Vijaya (International Surgery Journal, 2019)
Background: This study describes the concurrence of ventral hernia, cholelithiasis and uterine fibroid in females and ventral hernia, cholelithiasis and benign prostatic hypertrophy in males. Methods: This is a prospective observational study of 100 patients of ventral hernia, cholelithiasis and uterine fibroid in females and ventral hernia, cholelithiasis and benign prostatic hypertrophy in males. Results: In this study, ventral hernia, cholelithiasis and uterine fibroid in females and ventral hernia, cholelithiasis and benign prostatic hypertrophy in males were observed. Conclusions: This is to specify the presence of more than one symptom in a patient may suggest presence of multiple diseases.